Psychodynamics of work: Bibliometric mapping in 53 years of publications indexed in Scopus and agenda for future studies - Moreira, Ana Zenilce; Santos, Ana Cristina Batista dos (Contextus - Revista Contemporânea de Economia e Gestão, 2023)
The study aimed to map the bibliometric profile of publications on Psychodynamics of Work and propose an agenda for future studies. This was a quantitative research, using bibliometric methods proposed by Zupic and Cater (2015). The 195 publications located in Scopus, from 1970 to 2022, were analyzed using the VOSviewer software. For future studies, it is suggested to relate PDT with technology and precarious work, the future of work, diversity management, sustainable work, remote work, as well as Covid-19 and work. As for the subjects, it is suggested to conduct research with other health professionals, with informal workers, self-employed workers, casual workers, dangerous professions, liberal professionals, volunteers, interns, workers in the economy of the sea, teachers and outsourced workers.